The Angels and the jinn - Philips, Bilal; One Islam Production (N.S.W, Australia : One Islam Production, 2004)
The angels and jinns, looks at the Islamic viewpoint dealing with the nature of these creations and how they interact with our world
Title from title screen
Presenter : Bilal Philips
Keywords: Angels -- Islam; Jinn